REIMAJINASI POLITIK DALAM NOVEL RABET, RUNTUHNYA JERMAN TIMUR KARYA MARTIN JANKOWSKI - Taufiq, Akhmad (LITERA, 2016)
This study aims to describe the factors, ideological reconstruction process, and political reimagination process in a nationhood phenomenon of the reunification of Germany as a nation and a state. The data source was Rabet, Runtuhnya Jerman Timur, a novel by Martin Jankowski. The study employed the perspective of new historicism studies through three steps of analysis, namely the ideological dimension, discursive practice at the time the events occurred, and discursive practice in the present context. The results of the study suggest that the reunification of Germany as a nation is based on three factors, namely: (1) the presence of collective consciousness among the citizens of East Germany and West Germany to live together after they have lived apart for decades; (2) the awareness of the importance of ideological reconstruction for the country to be built, that is the presence of alternative political ideology in the third way; and (3) the political reimagination driven by racial dimension awareness enabling freedom to grow, violent acts to disappear, and welfare to be realized as envisioned ideals.